Clinical Predictors for Lack of Favorable Vascular Response to Statin Therapy in Patients With Coronary Artery Disease: A Serial Optical Coherence Tomography Study. Issue 11 (1st November 2017) - Minami, Yoshiyasu; Wang, Zhao; Aguirre, Aaron D.; Ong, Daniel S.; Kim, Chong‐Jin; Uemura, Shiro; Soeda, Tsunenari; Lee, Hang; Fujimoto, James; Jang, Ik‐Kyung
Abstract : Background: Previous studies have demonstrated that statin therapy improves cardiac outcomes, probably by stabilizing thin‐cap fibroatheroma in patients with coronary artery disease. However, major adverse cardiac events still occur in some patients, despite statin therapy. The aim of this study is to identify clinical predictors for the lack of a favorable vascular response to statin therapy in patients with coronary artery disease. Methods and Results: A total of 140 nonculprit plaques from 84 patients with coronary artery disease who were treated with a statin and had serial optical coherence tomography imaging (median interval, 6.3 months) were included. Thin‐cap area (fibrous cap thickness, <200 μm) was measured using a novel 3‐dimensional computer‐aided algorithm. Overall, the thin‐cap area significantly decreased from baseline (median, 2.852 mm 2 ; 25 th –75 th percentile, 1.023–6.157 mm 2 ) to follow‐up (median, 1.210 mm 2 ; 25 th –75 th percentile, 0.250–3.192 mm 2 ; P <0.001), and low‐density lipoprotein cholesterol significantly decreased from baseline (mean±SD, 92.9±30.1 mg/dL) to follow‐up (mean±SD, 76.3±23.3 mg/dL; P <0.001). The general linear model with multiple predictor variables revealed that the thin‐cap area was significantly higher in patients with chronic kidney disease than in those without it (regression coefficient b, 1.691 mm 2 ; 95% confidence interval, 0.350–3.033 mm 2 ; P =0.013) and lower in patients with acute coronary syndrome (regression coefficient b, −1.535 mm 2 ; 95% confidence interval, −2.561 to −0.509 mm 2 ; P =0.003). Conclusions: Chronic kidney disease is an independent predictor for the lack of a favorable vascular response to statin therapy, whereas acute coronary syndrome is an independent predictor for favorable vascular response to statin therapy. These findings should be further warranted in future prospective studies. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01110538.